Upaya Pemenuhan Hak Anak Binaan dalam Pengembangan Minat dan Bakat (Soft Skill) di Lembaga Pemasyarakatan Khusus Anak Kelas II Bengkulu - Dea Apriliandira; Rachel Syavira Sitohang; Yulistia Purnama Suci; Arie Elcaputera (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2025)
In order to improve the skills of children assisted by correctional facilities specifically for Class II Bengkulu children, training is regularly held to equip the children assisted so that after leaving they can be economically independent and have soft skills. Through this, it is hoped that they will not be confused because after leaving prison they already have the skills. The formulation of the problem in this research is 1) How are efforts to fulfill the rights of assisted children in developing interests and talents (soft skills) in special institutions for Class II Bengkulu 2) What are the obstacles in implementing the fulfillment of the rights of assisted children in developing interests and talents (soft skills) at the Bengkulu Class II Special Children's Institution. This research is empirical legal research using primary and secondary data types. The approaches in research are a statutory approach and a conceptual approach. The results of the research show that implementation has been carried out although not completely optimal and the obstacles are a lack of facilities and a lack of partners in fulfilling the rights of fostered children in developing their interests and talents.